Optimized bioconversion of grapeseed oil-based bioactive conjugated linoleic acid by Bacillus coagulans IBRC-M 10807 - Rezavand Hesari, Mana; Amiri, Saber; Asianezhad, Amirhossein; Khalili, Amin; Ho, Thao M.; Saris, Per E. J.; Yousefvand, Amin (Frontiers in Sustainable Food Systems, 2024)
Biosynthesizing conjugated linoleic acid (CLA) using food processing by-products offers a practical and efficient method for producing this valuable compound, delivering health benefits, promoting sustainability, and providing economic advantages. Here, we optimized the fermentation conditions for in situ biosynthesis of CLA using Bacillus coagulans IBRC-M 10807, with grapeseed oil by-product providing the linoleic acid precursor, focusing on temperature, pH, incubation time, concentrations of grapeseed oil and yeast extract. The total CLA was measured using a UV–Vis spectrophotometer at 233 nm, and the concentration was evaluated using a standard curve of conjugated linoleic acid. To analyze the isomers and identify the functional groups of biosynthesized CLA, gas chromatography (GC) and Fourier-transform infrared spectroscopy (FTIR) were used, respectively. The results indicated that the maximum amount of CLA production was 225.37 ± 0.74 μg/mL, obtained under optimal conditions: an initial pH of 6.8, a temperature of 44.8 °C, an incubation time of 48 h, a grapeseed oil concentration of 1000 μg/mL, and a yeast extract concentration of 3.88%. Characterization of the produced CLA revealed two main isomers – CLA 1: c-9, t-11 C18:2, and CLA 2: t-10, c-12 C18:2 methyl esters. These results suggest that B. coagulans has high potential to produce CLA as a bioactive compound, offering an excellent opportunity for use in various industries, including nutraceuticals, foods, pharmaceuticals, cosmetics, and animal feeds.